Pengaruh Perhatian Orang Tua di Masa Pandemi Covid-19 terhadap Hasil Belajar Matematika - Azizah, Nisa Rizky Noer; Isrokatun, Isrokatun; Sudin, Ali (Jurnal Pena Ilmiah, 2021)
Parental attention is very important, especially during the Covid-19 pandemic. So the purpose of this study was to determine the effect of parental attention during the Covid-19 pandemic on student learning outcomes in mathematics. This research is a quantitative research using survey method. The data collection technique used a parental attention questionnaire and documentation of the value of math report cards. Data analysis used linear regression analysis with one predictor. The results showed the average value of parental attention was 82.04 and for the percentage of 46.08% parents always guide their children in learning, 43.04% parents always motivate their children to learn, and 58.23% parents always provide learning facilities. As for the results of learning mathematics the average value is 82.40. Hypothesis testing shows that there is a significant effect between parental attention during the Covid-19 pandemic on mathematics learning outcomes. The contribution given by parents' attention to students' mathematics learning outcomes is 20.6%, the rest is due to the influence of other variables.